Application of the Talking Stick Learning Model to Improve Early Childhood Physical Motor Skills - Hadidja, Sitti; Herlina, Herlina; Bachtiar, Muhammad Yusri; Wahira, Wahira (PT. Riset Press International, 2025)
The Talking Stick learning model is interpreted as a learning model for playing sticks, designed to measure the mastery of learning materials, foster learning motivation and create a fun learning atmosphere for students by using sticks. This research focuses on the Application of the Talking Stick Learning Model by Utilizing Used Goods to Improve Physicalmotor Skills in Early Childhood. The purpose of this study is to find out the Application of the Talking Stick Learning Model by Utilizing Used Goods to Improve Children's Physicalmotor Skills after early childhood The type of research used is a type of qualitative research with a case study approach. The results of the study are as follows: 1) The Talking Stick learning model is implemented in early childhood, where teachers provide direct guidance. The application of the talking stick learning model is carried out in the process of activities that can improve children's oral language skills in the future As for the inhibiting factors in Talking Stick learning that